La inocuidad de alimentos y su relevancia en los tratados de libre comercio (TLC) - Guevara Lam, Ernesto (2025)
This article refers to food safety as an important issue on the framework of sanitary and phytosanitary measures and international trade. The study refers to sanitary and phytosanitary measures on multilateral scope—World Trade Organization—and its role on the treatment of food safety related to international trade among countries, and how it serves as platform for further developments in the context of the free trade agreements (FTAs), and in particular the FTAs signed by Peru. After the review of this issue at multilateral and bilateral/regional level, it is questioned whether it is necessary a specific provision on the FTAs about food safety or if its effective treatment can be done with the sustantive provisions about sanitary and phytosanitary measures of the FTAs.